Análise da progressão e da reversão de lesões artificiais de cárie através de espectroscopia Raman e tomografia de coerência óptica - Oliveira, Rosa Virginia Dutra de (2011)
There are several protocols for the development of artificial carious lesions, and pH-cycling models, involving the exposure of substrates to the combination of demineralization and remineralization, are the most used. Usually, the methodologies analysis of the lesions obtained based on surface changes, and no information is obtained for deeper layers. The aim of this study was to analyze the progression and the reversal of artificial carious lesions in human enamel. Fifty third molars were used to obtain one hundred enamel blocks. Treatment consisted of a demineralizer pH cycling for different periods of time: G1 (1 day), G2 (3 days), G3 (5 days), G4 (7 days), G5 (9 days) and G6 (11 days). The remineralizing treatment used pH cycling for 7 days and neutral 2% fluoride gel applications, on alternate days. The samples were analyzed before and after treatments using Raman Spectroscopy (RS) for the analysis of the content of calcium phosphate and Optical Coherence Tomography (OCT) for the analysis of morphological characteristics. After the demineralization treatment it was observed greater loss of calcium phosphate for G1 compared to the other groups. The results showed that G1 and G2 presented an unchanged surface after demineralization treatment; in G3 and G4 it was observed surface irregularities, indicating initial erosion of the enamel surface, which progressed, resulting in exposure of the underlying dentin (G6). Beneath of the surface there was a progressive demineralization, according to increasing periods of time, and the cervical region showed greater demineralization than the occlusal region. In respect to the loss and gain of calcium phosphate, it was observed mineral loss for G1 and G2 after the remineralization treatment, while G3, G4, G5 and G6 showed gain of calcium phosphate. The morphological analysis after remineralization showed that there were reversals of the process only for G5. Longer storage periods showed a gradual demineralization effect on the surface and subsurface of the enamel. The cervical region of the specimens was more sensitive to demineralization than did the occlusal region. Shorter periods of storage showed no response to remineralization treatment.